Peningkatan Kemampuan Pendampingan Anak Lapak Jati Padang Melalui Training Psychological First Aid (PFA) - Bambang Eko Samiono; Masni Erika Firmiana; Putri Februari (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
As a house for training programs and study groups for children of Jati Padang scavengers, Rumah Singgah Gemilang (RSG) not only faces problems with the educational program that is the purpose of their learning but also faces psychosocial problems of the scavengers.  Rumah Singgah, which is located in the scavenger neighborhood of Gang Saibun, Jatipadang, South Jakarta, is one of the Gemilang Indonesia Foundation program. There are 12 shelter children aged between 13 and 18 years old. The main problem faced by the administrators and  facilitators of RSG is the existence of various psychosocial problems of children who are relatively quite complex while the administrators and  facilitators of RSG do not have the basic skills to handle them.  The solution program provided is a Psychological First Aid (PFA) Training or Dampingan Psikologis Awal (DPA) to equip administrators and shelter children facilitators to provide initial psychological assistance for troubled shelter children. The implementation method is training and hands-on practice as well as online mentoring for 1 month. The results obtained are the development of 10 shelter children facilitators who understand and are able to practice the basics of PFA to shelter children. From the evaluation carried out, the value of the participant's satisfaction level is above 4.7 from a score of 5. the average increase in knowledge from the average pre-test score of 5 to an average of 8 in each session.